REGULATING AI IN INDONESIA: BETWEEN DIGITAL DREAMS AND POWER PLAYS - Angendari, D A Diah (AoIR Selected Papers of Internet Research, 2026)
The rapid development of artificial intelligence (AI) has prompted countries worldwide to craft policies and regulations that capture both the promise and peril of this transformative technology. While resource-rich nations and private-sector giants have been at the forefront of AI governance debates, many countries in the Global South are now joining the regulatory race. Indonesia offers a particularly instructive case. The country introduced a National AI Strategy in 2020 and a circular letter on AI Ethics in 2023, and is currently drafting a presidential regulation on AI governance. However, these efforts unfold amid mounting concerns that the country’s digital policies may be drifting toward authoritarian tendencies, raising questions about whose interests AI regulation ultimately serves. This study presents findings from a multi-sited ethnographic study examining the policy-making process behind Indonesia’s emerging AI regulations. By tracing how various policy actors, such as government officials, industry representatives, civil society organizations, think tanks, and academia, imagine AI, the research reveals how historical precedents, contemporary power structures, and global policy discourses shape the country’s AI governance. The study underscores that Indonesia’s AI policy is neither a straightforward adoption of Global North models nor a purely local affair. Instead, it reflects a dynamic interplay of political, economic, and technological interests that echo the country’s long-standing tradition of using information and communication technologies (ICTs) to project visions of modernity and consolidate elite power.